The Proactive-Reactive Resilience as a Mediational Variable Between the Character Strength and the Flourishing in Undergraduate Students - de la Fuente, Jesús; Urien, Begoña; Luis, Elkin O.; González-Torres, María Carmen; Artuch-Garde, Raquel; Balaguer, Alvaro (Frontiers in Psychology, 2022)
The aim of this research was to delimit the predictive and mediational model of resilience between character strengths to predict flourishing, in a sample of undergraduate students. After signing their informed consent, 642 university students completed three validated scales (i.e., character strengths, resilience and flourishing). Using an ex post facto design, regression, structural modelling, and mediation analyses were carried out, in order to construct a multi-causal predictive model. Results indicated a consistent predictive direct effect of character strengths on resilience and flourishing and of resilience on flourishing. As hypothesized, resilience also showed a mediating effect on the relationship between character strengths and flourishing. Additionally, results also revealed that the reactive and proactive factors of resilience were explained by different character strengths (e.g., emotional strength/cognitive, interpersonal strengths), reinforcing the idea that the two directions are complementary and necessary. Finally, several implications were established for the practice of positive psychology.